2020
DOI: 10.48550/arxiv.2009.03798
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of COVID-19 on relative changes in aggregated mobility using mobile-phone data

Abstract: Evaluating relative changes leads to additional insights that would remain hidden when only evaluating absolute changes. We analyze a dataset describing the mobility of mobile phones in Austria before, during COVID-19 lock-down measures until recently.By applying compositional data analysis we show that formerly hidden information becomes available: we see that the elderly population groups increase relative mobility and that the younger groups, especially on weekends, also do not decrease their mobility as mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…There is a mixed picture regarding the impacts of the pandemic on the mobility and activities of different genders. Some studies reported a higher rate of overall mobility and longer trips for men compared to women [ 6 , 12 , 44 ], while other studies reported a higher drop in men’s overall mobility [ 26 ] ( Table 3 ). Several studies identified an increase of car use and walking by women [ 10 , 11 ] and a decrease in PT, while there is also evidence of no significant change of mode choice during the pandemic between men and women [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a mixed picture regarding the impacts of the pandemic on the mobility and activities of different genders. Some studies reported a higher rate of overall mobility and longer trips for men compared to women [ 6 , 12 , 44 ], while other studies reported a higher drop in men’s overall mobility [ 26 ] ( Table 3 ). Several studies identified an increase of car use and walking by women [ 10 , 11 ] and a decrease in PT, while there is also evidence of no significant change of mode choice during the pandemic between men and women [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…People on low-income appeared less flexible in reducing their amount of travel through home-based working, while they continued using public transport during the pandemic at higher rates than people with higher incomes [ 10 , 15 , 23 ]. Moreover, females tended to take over increased housework and caring activities (e.g., of children and older people) during the pandemic, negatively affecting their ability to keep-up with their job activities [ 6 , 24 , 25 , 26 ]. The implications of COVID-19 for the mobility and activities of VSGs have attracted less attention in the scholarly literature compared to the respective changes of other social groups [ 6 , 7 , 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%